Fractures of angle of mandible – A retrospective study - Sourav Singh; Ramesh R. Fry; Ajit Joshi; Geeta Sharma; Smita Singh (Journal of Oral Biology and Craniofacial Research)
Aims: This retrospective study was done to evaluate the efficacy of single miniplate osteosynthesis at superior border of angle of mandible. Material and methods: In this study 50 patients were treated by single miniplate osteosynthesis according to Champy's principle. Bite force generated was used as a parameter for judging the efficacy of internal fixation. In this article we present our experience over the years in the management of the fractures of angle of mandible based on this model. Results: Most patients were of 21–30 yrs of age with unilateral angle fracture of mandible except one patient who had isolated bilateral angle fracture. The patients were treated successfully according to Champy's principle of osteosynthesis. There was a progressive improvement in the bite force generated after osteosynthesis. Conclusions: The angle of the mandible is an anatomically weak and an area susceptible to fracture. The presence of an impacted or partially erupted third molar tooth further weakens it. Angle of mandible is the most common site for fracture however, bilateral angle fracture is very rare and uncommon.Osteosynthesis according to Champy's model led to an early functional improvement as demonstrated by the bite force generated.